Impact of dexmedetomidine on amino acid contents and the cerebral ultrastructure of rats with cerebral ischemia-reperfusion injury - Lin,Sheng (2017)
Abstract Purpose: To investigate the effects of dexmedetomidine (DEX) on amino acid contents and the cerebral ultrastructure of rats with cerebral ischemia-reperfusion injury (I/R). Methods: Thirty-six, male, Wistar rats were randomly divided into three groups: the sham operation group (group C), the ischemia-reperfusion group (group I/R), and the DEX group (group D). The middle cerebral artery occlusion model was prepared by the modified Longa method. The time of ischemia was 180 min, and 120 min after reperfusion, the amount of glutamate (Glu), and γ-aminobutyric acid (GABA) in the brain were measured, and the ultrastructure-level changes in the cerebral cortex were examined using electron microscopy. Results: Compared to group C, Glu contents in group D, and I/R significantly increased. Compared to group I/R, Glu contents in group D significantly decreased. Compared to group C, GABA contents in group D, and I/R significantly increased, and those in group D significantly increased, as compared to group I/R. The cerebral ultrastructure was normal in group C. Vacuolar degeneration in the plastiosome and nervous processes, was more critical than in group D. Vascular endothelial cells (VEC) were damaged. On the contrary, these changes in group D significantly improved. Conclusion: Dexmedetomidine is capable of decreasing glutamergic content, and increasing GABAergic content, in order to decrease the injury of the cerebral ultrastructure, following cerebral ischemia-reperfusion injury.